Validation of the YLS/CMI on an Australian Juvenile Offending Population - Dellar, Kristie (International journal of offender therapy and comparative criminology, 2023)
There is a wealth of research that shows juvenile justice systems that utilize structured and validated assessment tools, such as the YLS/CMI, are far more effective at reducing rates of recidivism than those who do not. In line with this research, the Department of Justice (DoJ) in Western Australia adopted the YLS/CMI as the standard risk assessment tool for evaluating the criminogenic risk and needs of youth entering the justice system. While there is evidence supporting the utility of the YLS/CMI in predicting recidivism, there is little research demonstrating its effectiveness in Australian juvenile populations and no such research in a West Australian population. There is also a lack of research on the utility of the tool with young Indigenous offenders, which is particularly concerning given the significant overrepresentation of Indigenous people in the Australian criminal justice system. Our study was the first to examine the reliability and predictive validity of the YLS/CMI on a sample of West Australian juvenile offenders. In this paper, we present the results of two analyses. The first examines the properties of the YLS/CMI in a cohort of 4,653 juvenile offenders in Western Australia, including factor structure, internal consistency, and differences between male and female youth and between Indigenous and non-Indigenous youth. Consistent with our hypotheses, the tool demonstrated excellent internal consistency (α = .91) and cross-validation analyses identified significant differences between groups on total YLS scores and risk domains. The second analysis examines the predictive validity of the YLS/CMI in a subsample of 921 youth with a minimum follow-up period of 2 years. The overall recidivism rate was 74.8% and there were differences in scores and recidivism rates for Indigenous compared to non-Indigenous youth, although the predictive accuracies in terms of AUC were similar (c. = 0.65 and 0.66, respectively).